Supervision of the Riau Province Plantation Service in Determining the Purchase Price of Fresh Fruit Bunches (FFB) in Siak Regency - Hakim, Arif Rahman; Tutrianto, Rio; Permana, Muh Dwi Agus (Doctoral Program of Social Science Pasundan University, 2025)
Siak Regency in Riau Province, as one of the regions with the largest potential for oil palm plantations in Indonesia, has the responsibility and authority to regulate the governance of this sector. The pattern of oil palm plantation business management in Riau Province is developed in the form of State Large Plantations (PBN), Private Large Plantations (PBS), and Smallholder Plantations. Fair and transparent pricing of Fresh Fruit Bunches (FFB) of oil palm is essential to ensure the welfare of smallholders, especially in Siak Regency, which has a significant area of ??oil palm plantations. The study uses the theory by George Roberts Terry regarding supervision with indicators for determining standards, measuring implementation, comparing implementation with standards, and correcting deviations. The research method used in this study is a qualitative method with descriptive analysis. The data sources in this study are primary data through observation and interviews and supported by secondary data through literature studies. The selection of research informants through purposive sampling. The results of the study indicate that there are still obstacles in company compliance with the set prices and that supervision is not optimal. This study recommends increased supervision, transparency in pricing, and strict sanctions for companies that violate the rules. With these improvements, it is hoped that regulations will be more in favor of farmers and create a fairer system.